Increase the Sugar Concentration of the Solution Sugar by Reverse Osmotic Membrane - Sri Redjeki; Nur Hapsari; Iriani (Nusantara Science and Technology Proceedings)
Sugar is one of the basic needs of people and food and drink industry. As technology advances and the demand for efficient usage of sugar rises, crystal sugar is seen as less advantageous than liquid sugar. If sugar is always dissolved in water before use, then it will be more efficient and practical for consumers to use sugar in liquid form than in crystal form. Other than that, liquid sugar is also attractive to consumers because it is economical, hygienic, instantly soluble in hot and cold water, fresher and longer-lasting, able to thicken and enrich the texture of foods and drinks, and functions as sweetener, syrup, and flavor enhancer. Liquid sugar is also more beneficial for sugar producers because of simpler production process, cheaper production cost, and similar yield with no extra cost. In sugar production, separation process is found in most of its stages and therefore the use of membrane technology for separating solute and water content has a good potential. In this research, water content reduction of sugar solution was done in order to increase the sugar concentration of the solution. The parameters of this research were 4%, 5%, and 6% starting concentration of sugar solution; 20, 40, and 60 minutes of process time; and 85 and 60 PSI ?P. The best result was acquired on 4% starting concentration, 60 PSI ?P, and 60 minutes process time.